Identification and characterization of extrachromosomal circular DNA in patients with high myopia and cataract. Issue 1 (31st December 2023) - Wen, Kai; Zhang, Lujie; Cai, Yang; Teng, He; Liang, Jingli; Yue, Yi; Li, Yaoling; Huang, Yifang; Liu, Ming; Zhang, Yufeng; Wei, Ruihua; Sun, Jing
ABSTRACT: To explore the presence of extrachromosomal circular DNA (eccDNA) in the anterior capsule of the lens in the eyes of patients with cataract and with high myopia. Circle-Seq was performed to identify differences in the eccDNA and gene expression between the anterior capsule of the lens of patients with simple nuclear cataract (C, n  = 6 cases) and patients with nuclear cataract along with high myopia (HM, n  = 6 cases). The expression of eccDNA was confirmed using routine quantitative polymerase chain reaction. The eccDNA ranked in C and HM ranged in length from 0.017 kb − 9.9 Mb with two distinctive peaks detected at 0.2 kb and 0.5 kb, while eccDNA that were differentially expressed ranged in size from 0.05 kb − 57.8 kb with two distinctive peaks observed at 0.1 kb and 0.5 kb. Only 2.5% of the eccDNA in C and 2% in HM were>25 kb in size. The gene-rich chromosomes contributed to more number of eccDNA/Mb, while several well-known high myopia candidate genes, including catenin delta 2 ( CTNND2 ) and ubiquitin-like with PHD, exhibited significantly increased levels of eccDNA in the anterior capsule of the lens in patients with high myopia. This study highlighted the topologic analysis of the anterior capsule of eyes with high myopia, which is an emerging direction for research and clinical applications. These findings suggested that eccDNA was commonly detected in eyes with high myopia and cataracts, and the candidate genes for high myopia identified in previous studies were also observed in the eccDNA.